2004
DOI: 10.1029/2003wr002706
|View full text |Cite
|
Sign up to set email alerts
|

Inverse modeling of large‐scale spatially distributed vadose zone properties using global optimization

Abstract: [1] Computational capabilities have evolved to a point where it is possible to use multidimensional physically based hydrologic models to study spatial and temporal patterns of water flow in the vadose zone. However, models based on multidimensional governing equations have only received limited attention, in particular because of their computational, distributed input, and parameter estimation requirements. The aim of the present paper is to explore the usefulness and applicability of the inverse method to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
83
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 65 publications
0
83
0
Order By: Relevance
“…The simulation results of MODHMS were compared with those obtained using a simple storage-based bucket model and a spatially averaged 1D flow model. The study concluded that the drain conductance and the bypass coefficient were determined well (while soil hydraulic properties were not) and that these parameters dominated the hydrology of the Broadview Water District (Vrugt et al, 2004). However, the conclusions about PF remain uncertain, since the simple bucket model gave similar results.…”
Section: Hillslope Scalementioning
confidence: 95%
See 1 more Smart Citation
“…The simulation results of MODHMS were compared with those obtained using a simple storage-based bucket model and a spatially averaged 1D flow model. The study concluded that the drain conductance and the bypass coefficient were determined well (while soil hydraulic properties were not) and that these parameters dominated the hydrology of the Broadview Water District (Vrugt et al, 2004). However, the conclusions about PF remain uncertain, since the simple bucket model gave similar results.…”
Section: Hillslope Scalementioning
confidence: 95%
“…MODHMS (Panday and Huyakorn, 2004) was applied with global inverse parameter optimization to simulate spatially distributed tile drainage for a 2-year period in the Broadview Water District (38.8 km 2 ), San Joaquin Valley, California (Vrugt et al, 2004). The domain was horizontally discretized into 200 m × 200 m square cells, which were vertically subdivided into 14 layers of 0.3 m (top) to 0.9 m (bottom).…”
Section: Hillslope Scalementioning
confidence: 99%
“…One of the major reasons to apply inverse modeling is to estimate parameters that cannot be directly measured for various reasons. Numerous applications of inverse modeling for the estimation of soil hydraulic properties exist in the literature (Abbaspour et al, 2004;Hopmans et al, 2002;Vrugt et al, 2008Vrugt et al, , 2004. The gradient methods (Marquardt, 1963) have been used most widely among hydrologists and soil scientists.…”
Section: Particle Swarm Optimizationmentioning
confidence: 99%
“…Numerous applications of inverse modeling for the estimation of soil hydraulic properties exist in the literature (Abbaspour et al, 2004;Hopmans et al, 2002;Vrugt et al, 2008;Vrugt et al, 2004). The gradient methods (Marquardt, 1963) have been most widely used among hydrologists and soil scientists.…”
Section: Particle Swarm Optimizationmentioning
confidence: 99%